Neuartiger Ansatz zum Richten von zwei- und dreidimensionalen Fehlern an einem Federdraht - Bathelt, Lukas; Djakow, Eugen; Dahms, Frederik; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Ilmenauer Federntag 2023: Neueste Erkenntnisse zu Funktion, Berechnung, Prüfung und Gestaltung von Federn und Werkstoffen)

Learning the Automated Setup of Profile Wrapping Lines for New Products from Few Past Setups - Koppert, Steven; Bause, Maximilian; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Lithium niobate waveguide squeezer with integrated cavity length stabilisation for network applications - Stefszky, M.; vom Bruch, F.; Santandrea, M.; Ricken, R.; Quiring, V.; Eigner, C.; Herrmann, H; Silberhorn, C (Optics Express)
We report a titanium indiffused waveguide resonator featuring an integrated electro-optic modulator for cavity length stabilisation that produces close to 5 dB of squeezed light at 1550 nm (2.4 dB directly measured). The resonator is locked on resonance for tens of minutes with 70 mW of SH light incident on the cavity, demonstrating that photorefraction can be mitigated. Squeezed light production concurrent with cavity length stabilisation utilising the integrated EOM is demonstrated. The device demonstrates the suitability of this platform for squeezed light generation in network applications, where stabilisation to the reference field is typically necessary.
Keywords: Atomic and Molecular Physics; and Optics

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

Analysis and Optimization of Joint Formation in Hybrid Compression Molding - Lückenkötter, Julian; Aydin, Simon; Marten, Thorsten; Tröster, Thomas

Evidence-based practices in teaching - Rybska, Eliza; Dudziak, Renata; Pollmeier, Pascal (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.

Wer übernimmt Verantwortung für Inklusion? - Kottmann, Brigitte; Lütje-Klose, Birgit; Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Bildungspolitik; Schulentwicklung; Sonderpädagogik

Elektrooptischer Balun und System zur Generierung eines pseudodifferentiellen Signals aufweisend einen solchen elektrooptischen Balun - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Balun, wobei der elektrooptische Balun einen Eingang für ein optisches Eingangssignal (Ein(t)) aufweist, wobei der elektrooptische Balun weiterhin ein 1x2 Multimodeninterferometer (1x2 MMI) und einen Phasenschieber (Δϕ) aufweist, wobei das 1x2 Multimodeninterferometer (1x2 MMI) mit dem Eingangssignal im Betrieb versorgbar ist, wobei der elektrooptische Balun weiterhin ein 2x4 Multimodeninterferometer (2x4 MMI) aufweist, wobei das 2x4 Multimodeninterferometer (2x4 MMI) mit den Ausgangsarmen des 1x2 Multimodeninterferometer (1x2 MMI) verbunden ist, wobei der Phasenschieber (Δϕ) in einem Ausgangsarm des 1x2 Multimodeninterferometer (1x2 MMI) angeordnet ist, wobei im Betrieb an zwei Ausgängen (Eout,1 (t), Eout,4(t)) des 2x4 Multimodeninterferometers (2x4 MMI) ein quasi differentielles optisches Signal anliegt, das mittels einer jeweiligen Photodiode (PD1, PD2) und einem differentiellen Schaltkreis in ein DC-freies elektrisches Signal (Vout) überführt werden kann. Weiterhin betrifft die Erfindung ein System zur Generierung eines pseudeodifferentiellen Signals, aufweisend einen elektrooptischen Balun sowie einen optischen Strahlteiler (OS) sowie einen dual output carrier injection Mach Zehnder Modulator (MZM), wobei der optische Strahlteiler (OS) ein Eingangssignal (IIN) in einen ersten Teil (n) und einen zweiten Teil (1-n) aufteilt, wobei der zweite Teil (1-n) als Eingangssignal (Ein(t)) im Betrieb auf den Eingang des elektrooptischen Baluns geführt wird, wobei der erste Teil (n) im Betrieb als Eingangssignal dem dual output carrier injection Mach Zehnder Modulator (MZM) zugeführt wird, wobei das quasi differentielle elektrische Signal (I1, I2) der Photodioden (PD1, PD2) im Betrieb zur Ansteuerung des dual output carrier injection Mach Zehnder Modulator (MZM) in push pull Konfiguration verwendet wird.

Elektrooptischer Mischer - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Mischer (1) mit elektrischem Ausgang, aufweisend: • eine Photodiode (PD), • einen ersten Anschluss, • einen zweiten Anschluss, • wobei die Anschlüsse eine erste Spannungsversorgung (V1) und eine zweite Spannungsversorgung (V2) oder eine erste Stromversorgung (I1) und eine zweite Stromversorgung (I2) anschließbar ist, • einen Anschluss für ein Kleinsignal-Massepotential, • ein erstes Teilanpassungsnetzwerk (Z2, Z4), welches auf der Anodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des ersten Teilanpassungsnetzwerkes (Z2) mit dem Anschluss für die zweite Spannungsversorgung (V2) schaltbar (S2) verbindbar ist, und wobei ein anderer Teil des ersten Teilanpassungsnetzwerkes (Z4) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S2') verbindbar ist, • ein zweites Teilanpassungsnetzwerk (Z1, Z3), welches auf der Kathodenseite der Photodiode (PD) angeordnet ist, wobei ein Teil des zweiten Teilanpassungsnetzwerkes (Z1) mit dem Anschluss für die erste Spannungsversorgung (V1) schaltbar (S1) verbindbar ist, und wobei ein anderer Teil des zweiten Teilanpassungsnetzwerkes (Z3) mit dem Anschluss für das Kleinsignal-Massepotential schaltbar (S1') verbindbar ist, • ein erstes entkoppelndes Element (C1) angeordnet auf der Kathodenseite und ein zweites entkoppelndes Element (C2) angeordnet auf der Anodenseite der Photodiode (PD), • wobei zwischen den von der Photodiode (PD) abgewandten Seiten des ersten entkoppelnden Elementes (C1) und des zweiten entkoppelnden Elementes (C2) im Betrieb einelektrisches Ausgangssignal bereitgestellt werden kann.

ENHANCED PLL CIRCUIT - Iftekhar, Mohammed; Scheytt, J. Christoph

Photonic Quantum Enhanced Radar Systems - Kruse, Stephan

Einfluss von Infrarotschweißprozessparametern auf die quasistatische und zyklische Belastbarkeit von technischen glasfaserverstärkten Thermoplasten - Gevers, Karina; Töws, P.; Schraa, L.; Decker, J.; Schöppner, Volker; Uhlig, K.; Stommel, M. (11. Landshuter Leichtbau-Colloquium)

A NEW APPROACH FOR THE LOCAL DETERMINATION OF ENERGY INPUT IN CO-ROTATING TWIN SCREW EXTRUDERS BASED ON SCREW TORSION - Schöppner, Volker; Austermeier, Laura; Nordieker, A.

Development Of An Asymmetric Torque Model For The Two Screws Of A Twin Screw Extruder - Schöppner, Volker; Austermeier, Laura; Alsoud, A.

Auswirkungen unterschiedlicher Erwärmstrategien auf infraroterwärmte Polyphthalamide - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J. (Joining Plastics)

Devulkanisation schwefelvernetzender Elastomere im halbleitergestützten Mikrowellenverfahren - Schöppner, Volker; Petzke, J.

Numerical investigations of new low‐order explicit last stage diagonal implicit Runge–Kutta schemes with the finite‐element method - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Abstract Initial value problems can be solved efficiently by means of Runge–Kutta algorithms with adaptive step size control. Diagonally implicit Runge–Kutta (DIRK) methods are the most popular class among the diverse family of Runge–Kutta algorithms. In this paper, the novel class of low‐order explicit last‐stage diagonally implicit Runge–Kutta (ELDIRK) methods are explored, which combine implicit schemes with an additional explicit evaluation as an explicit last stage. ELDIRK Butcher tableaus are used to control embedded RK methods to obtain solutions of different orders. The lower‐order solution is obtained by classical implicit RK stages and the higher‐order solution is obtained by additional explicit evaluation. As a result, a significant reduction in computational cost is achieved by skipping the iterative solution of nonlinear systems for the additional step. The examination of the heat problem and the use of the innovative Butcher tableau in the finite‐element method are the main contributions of this work. Thus, it is possible to establish adaptive step size control for the new low‐order embedded methods based on an empirical method for error estimation. Two‐dimensional simulations are used to show an appropriate algorithm for the ELDIRK schemes. The new Runge–Kutta schemes' predictions of higher‐order convergence are confirmed, and their successful outcomes are illustrated.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

No effects of different perturbations on the performance in a mental body-rotation task (MBRT) with egocentric perspective transformations and object-based transformations - Budde, Kirsten; Weigelt, Matthias (Human Movement Science)
The present study investigates participants' performance in two different mental body-rotation tasks (MBRTs) under conditions in which dynamic stability is challenged in two different balancing conditions: active balance control (Experiment 1), where participants actively maneuver, and re-active balance control (Experiment 2), where participants react to an external perturbation. The two MBRTs induced either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment). In Experiment 1, 48 participants were tested while standing on an even ground (low balancing requirements) or on a balance board (high balancing requirements). In Experiment 2, 32 participants performed while either standing still on a vibration plate or with the vibration plate moving in a low (20 Hz) or high (180 Hz) frequency. In both experiments, the results for response time and response error revealed effects of rotation angle and type of task. An effect of balancing condition was only observed for response error in Experiment 1. More precisely, response times and response errors increased for higher rotation angles. Also, performance was better for egocentric than for object-based spatial transformations. However, the different challenges to dynamic stability in Experiments 1 and 2 did not influence performance in the two MBRTs (except for response errors in Experiment 1) nor in a control condition (Experiment 1) without mental rotation.
Keywords: Mental rotation; Balance control; Perturbation; Embodiment

Rezension: Erika Thomalla: Anwälte des Autors. Zur Geschichte der Herausgeberschaft im 18. und 19. Jahrhundert, Göttingen: Wallstein 2020 und Ines Barner: Von anderer Hand. Praktiken des Schreibens zwischen Autor und Lektor, Göttingen: Wallstein 2021 - Spener, Anna Maria; Heimgartner, Stephanie (Sprache und Literatur)

Investigation of the Volume Flow in the FFF Process as an Influencing Factor on the Resulting Orientation of Thermally Conductive Filler Particles - Moritzer, Elmar; Elsner, Christian Lennart; Deupmann, K.

Investigation of the influence of screw geometry on the resulting melt quality for cast film extrusion - Schöppner, Volker; Trienens, Dorte

Großflächig, komplex? InMould-Plasma ist die Lösung! - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Rauen, Dennis; Kolbe, B.; Schlee, H.; Hokamp, C. (Kunststoffe)

Goodbye Hot Spots - with No Extra Energy Expenditure - Moritzer, Elmar; Kartelmeyer, Stephan; Kreamer, Dennis; Jaroschek, Christoph (Plastics Insights)

Hauptsache, die Wellenlänge stimmt - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

Hotspots ade - ohne Extra-Energieaufwand - Moritzer, Elmar; Kartelmeyer, Stephan; Kraemer, Dennis; Jaroschek, Christoph (Kunststoffe)

Optimization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian

Optimisation of the Simulation of Rubber Extrusion dies by means of the Integration of empirically determined characteristic Maps - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Wiesel, C.; Nillius, U.; Schön, M.; Limper, A. (KGK Kautschuk Gummi Kunststoffe)

Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Methoden zur Förderung von Kompetenzen für eine demokratische Kultur - Schriftliche Reflexionen von Lehramtsstudierenden aus bildungswissenschaftlichen Seminaren - Wehde, Janis; Bloh, Bea

Wie war das damals? Oral history und Zeitzeug:innenbefragung - Diederich, Julia ((Über-)Leben im Nationalsozialismus)

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (Physical Review B)

“I do not know! but why?” — Local model-agnostic example-based explanations of reject - Artelt, André; Visser, Roel; Hammer, Barbara (Neurocomputing)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Warum es ein Marketing für die Berufsbildung braucht – Zwei Fallstudien über die Verbesserung der Durchlässigkeit durch innovative Fortbildungen auf der DQR-Stufe 5 - Peitz, Nina-Madeleine; Müller-Wegner, Max; Ertl, Hubert
Mittels Fallstudien zweier Projekte des bundesweiten Programms InnoVET (Zukunft gestalten – Innovationen für eine exzellente berufliche Bildung) wird untersucht, wie innovative Aufstiegsfortbildungen auf der DQR-Stufe 5 zu einer durchlässigeren Berufsbildung im Verbund gestaltet und Ergebnisse transferiert werden. Zwecks nachhaltiger Implementation am Markt wird der Bedarf eines Marketings deutlich.

Segment-Less Continuous Speech Separation of Meetings: Training and Evaluation Criteria - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Continuous Speech Separation (CSS) has been proposed to address speech overlaps during the analysis of realistic meeting-like conversations by eliminating any overlaps before further processing. CSS separates a recording of arbitrarily many speakers into a small number of overlap-free output channels, where each output channel may contain speech of multiple speakers. This is often done by applying a conventional separation model trained with Utterance-level Permutation Invariant Training (uPIT), which exclusively maps a speaker to an output channel, in sliding window approach called stitching. Recently, we introduced an alternative training scheme called Graph-PIT that teaches the separation network to directly produce output streams in the required format without stitching. It can handle an arbitrary number of speakers as long as never more of them overlap at the same time than the separator has output channels. In this contribution, we further investigate the Graph-PIT training scheme. We show in extended experiments that models trained with Graph-PIT also work in challenging reverberant conditions. Models trained in this way are able to perform segment-less CSS, i.e., without stitching, and achieve comparable and often better separation quality than the conventional CSS with uPIT and stitching. We simplify the training schedule for Graph-PIT with the recently proposed Source Aggregated Signal-to-Distortion Ratio (SA-SDR) loss. It eliminates unfavorable properties of the previously used A-SDR loss and thus enables training with Graph-PIT from scratch. Graph-PIT training relaxes the constraints w.r.t. the allowed numbers of speakers and speaking patterns which allows using a larger variety of training data. Furthermore, we introduce novel signal-level evaluation metrics for meeting scenarios, namely the source-aggregated scale- and convolution-invariant Signal-to-Distortion Ratio (SA-SI-SDR and SA-CI-SDR), which are generalizations of the commonly used SDR-based metrics for the CSS case.
Keywords: Continuous Speech Separation; Source Separation; Graph-PIT; Dynamic Programming; Permutation Invariant Training

On Word Error Rate Definitions and Their Efficient Computation for Multi-Speaker Speech Recognition Systems - von Neumann, Thilo; Boeddeker, Christoph; Kinoshita, Keisuke; Delcroix, Marc; Haeb-Umbach, Reinhold (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
We propose a general framework to compute the word error rate (WER) of ASR systems that process recordings containing multiple speakers at their input and that produce multiple output word sequences (MIMO). Such ASR systems are typically required, e.g., for meeting transcription. We provide an efficient implementation based on a dynamic programming search in a multi-dimensional Levenshtein distance tensor under the constraint that a reference utterance must be matched consistently with one hypothesis output. This also results in an efficient implementation of the ORC WER which previously suffered from exponential complexity. We give an overview of commonly used WER definitions for multi-speaker scenarios and show that they are specializations of the above MIMO WER tuned to particular application scenarios. We conclude with a discussion of the pros and cons of the various WER definitions and a recommendation when to use which.
Keywords: Word Error Rate; Meeting Recognition; Levenshtein Distance

MeetEval: A Toolkit for Computation of Word Error Rates for Meeting Transcription Systems - von Neumann, Thilo; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (Proc. CHiME 2023 Workshop on Speech Processing in Everyday Environments)
MeetEval is an open-source toolkit to evaluate all kinds of meeting transcription systems. It provides a unified interface for the computation of commonly used Word Error Rates (WERs), specifically cpWER, ORC WER and MIMO WER along other WER definitions. We extend the cpWER computation by a temporal constraint to ensure that only words are identified as correct when the temporal alignment is plausible. This leads to a better quality of the matching of the hypothesis string to the reference string that more closely resembles the actual transcription quality, and a system is penalized if it provides poor time annotations. Since word-level timing information is often not available, we present a way to approximate exact word-level timings from segment-level timings (e.g., a sentence) and show that the approximation leads to a similar WER as a matching with exact word-level annotations. At the same time, the time constraint leads to a speedup of the matching algorithm, which outweighs the additional overhead caused by processing the time stamps.
Keywords: Speech Recognition; Word Error Rate; Meeting Transcription

Schnittstelle zwischen Programmen und Forschung – Die Forschungsbegleitung InnoVET - Ertl, Hubert; Peitz, Nina-Madeleine (Datenreport zum Berufsbildungsbericht 2023. Informationen und Analysen zur Entwicklung der beruflichen Bildung)

Berufliche Fortbildung – gleichwertige Alternativen zum Hochschulabschluss. Erste Erkenntnisse aus dem Innovationswettbewerb InnoVET - Bednarz, Sigrid; Martens, Stephanie; Peitz, Nina-Madeleine (Berufsbildung in Wissenschaft und Praxis)

Komponierte Ambiguität. Ein anderer Blick auf polyphone Messen des 15. und 16. Jahrhunderts - Höink, Dominik (Kirchenmusikalisches Jahrbuch)

A Memetic NSGA-II for the Multi-Objective Flexible Job Shop Scheduling Problem with Real-time Energy Tariffs - Burmeister, Sascha Christian; Guericke, Daniela; Schryen, Guido (Flexible Services and Manufacturing Journal)

‘I had a patient who…’: Narratives of Vicarious Experience in GPs’ Discourse on Domestic Violence - Mildorf, Jarmila (Narrative Structure and Narrative Knowing in Medicine and Science)

Class Expression Learning with Multiple Representations - Ngonga Ngomo, Axel-Cyrille; Demir, Caglar; Kouagou, N'Dah Jean; Heindorf, Stefan; Karalis, Nikoloas; Bigerl, Alexander (Compendium of Neurosymbolic Artificial Intelligence)

Anmerkungen zum Begriff des digitalen Kapitalismus. - Christian, Fuchs (Theorien des digitalen Kapitalismus)

Spatial Diarization for Meeting Transcription with Ad-Hoc Acoustic Sensor Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Proc. Asilomar Conference on Signals, Systems, and Computers)
We propose a diarization system, that estimates “who spoke when” based on spatial information, to be used as a front-end of a meeting transcription system running on the signals gathered from an acoustic sensor network (ASN). Although the spatial distribution of the microphones is advantageous, exploiting the spatial diversity for diarization and signal enhancement is challenging, because the microphones’ positions are typically unknown, and the recorded signals are initially unsynchronized in general. Here, we approach these issues by first blindly synchronizing the signals and then estimating time differences of arrival (TDOAs). The TDOA information is exploited to estimate the speakers’ activity, even in the presence of multiple speakers being simultaneously active. This speaker activity information serves as a guide for a spatial mixture model, on which basis the individual speaker’s signals are extracted via beamforming. Finally, the extracted signals are forwarded to a speech recognizer. Additionally, a novel initialization scheme for spatial mixture models based on the TDOA estimates is proposed. Experiments conducted on real recordings from the LibriWASN data set have shown that our proposed system is advantageous compared to a system using a spatial mixture model, which does not make use of external diarization information.
Keywords: Diarization; time difference of arrival; ad-hoc acoustic sensor network; meeting transcription

Additive Manufacturing and Mechanical Properties of Auxetic and Non-Auxetic Ti24Nb4Zr8Sn Biomedical Stents: A Combined Experimental and Computational Modelling Approach - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
The effect of plaque deposition (atherosclerosis) on blood flow behaviour is investigated via computational fluid dynamics and structural mechanics simulations. To mitigate the narrowing of coronary artery atherosclerosis (stenosis), the computational modelling of auxetic and non-auxetic stents was performed in this study to minimise or even avoid these deposition agents in the future. Computational modelling was performed in unrestricted (open) conditions and restricted (in an artery) conditions. Finally, stent designs were produced by additive manufacturing, and mechanical testing of the stents was undertaken. Auxetic stent 1 and auxetic stent 2 exhibit very little foreshortening and radial recoil in unrestricted deployment conditions compared to non-auxetic stent 3. However, stent 2 shows structural instability (strut failure) during unrestricted deployment conditions. For the restricted deployment condition, stent 1 shows a higher radial recoil compared to stent 3. In the tensile test simulations, short elongation for stent 1 due to strut failure is demonstrated, whereas no structural instability is noticed for stent 2 and stent 3 until 0.5 (mm/mm) strain. The as-built samples show a significant thickening of the struts of the stents resulting in short elongations during tensile testing compared to the simulations (stent 2 and stent 3). A modelling framework for the stent deployment system that enables the selection of appropriate stent designs before in vivo testing is required. This leads to the acceleration of the development process and a reduction in time, resulting in less material wastage. The modelling framework shall be useful for doctors designing patient-specific stents.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Post-Processing Independent Evaluation of Sound Event Detection Systems - Ebbers, Janek; Haeb-Umbach, Reinhold; Serizel, Romain (Proceedings of the 8th Detection and Classification of Acoustic Scenes and Events 2023 Workshop (DCASE2023))
Due to the high variation in the application requirements of sound event detection (SED) systems, it is not sufficient to evaluate systems only in a single operating mode. Therefore, the community recently adopted the polyphonic sound detection score (PSDS) as an evaluation metric, which is the normalized area under the PSD receiver operating characteristic (PSD-ROC). It summarizes the system performance over a range of operating modes resulting from varying the decision threshold that is used to translate the system output scores into a binary detection output. Hence, it provides a more complete picture of the overall system behavior and is less biased by specific threshold tuning. However, besides the decision threshold there is also the post-processing that can be changed to enter another operating mode. In this paper we propose the post-processing independent PSDS (piPSDS) as a generalization of the PSDS. Here, the post-processing independent PSD-ROC includes operating points from varying post-processings with varying decision thresholds. Thus, it summarizes even more operating modes of an SED system and allows for system comparison without the need of implementing a post-processing and without a bias due to different post-processings. While piPSDS can in principle combine different types of post-processing, we here, as a first step, present median filter independent PSDS (miPSDS) results for this year’s DCASE Challenge Task4a systems. Source code is publicly available in our sed_scores_eval package (https://github.com/fgnt/sed_scores_eval).

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, D.; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

"Would You Give the Same Priority to the Bank and a Game? I Do Not!" Exploring Credential Management Strategies and Obstacles during Password Manager Setup - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Acar, Yasemin; Fahl, Sascha (Nineteenth Symposium on Usable Privacy and Security, SOUPS 2023, Anaheim, CA, USA, August 5-7, 2023)

"I wouldn’t want my unsafe code to run my pacemaker": An Interview Study on the Use, Comprehension, and Perceived Risks of Unsafe Rust - Höltervennhoff, Sandra; Klostermeyer, Philip; Wöhler, Noah; Acar, Yasemin; Fahl, Sascha (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

Ethical Frameworks and Computer Security Trolley Problems: Foundations for Conversations - Kohno, Tadayoshi; Acar, Yasemin; Loh, Wulf (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

Who Comes Up with this Stuff? Interviewing Authors to Understand How They Produce Security Advice - Neil, Lorenzo; Sri Ramulu, Harshini; Acar, Yasemin; Reaves, Bradley (Nineteenth Symposium on Usable Privacy and Security, SOUPS 2023, Anaheim, CA, USA, August 5-7, 2023)

Beyond the Boolean: How Programmers Ask About, Use, and Discuss Gender - Bouma-Sims, Elijah; Acar, Yasemin (Proc. ACM Hum. Comput. Interact.)

Beyond the Boolean: How Programmers Ask About, Use, and Discuss Gender - Bouma-Sims, Elijah; Acar, Yasemin (CoRR)

"Make Them Change it Every Week!": A Qualitative Exploration of Online Developer Advice on Usable and Secure Authentication - Klemmer, Jan H.; Gutfleisch, Marco; Stransky, Christian; Acar, Yasemin; Sasse, M. Angela; Fahl, Sascha (CoRR)

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

Kant and the Role(s) of Doctrines of Methods (Journal of Transcendental Philosophy)

Your Smartphone Is Watching You - Eine technikkritische Untersuchung der menschlichen Freiheit und Antiquiertheit im Zeitalter der Digitaltechnologie - Mac Award, Daria-Leona

Im Dialog: Theologische Grundlagen und religionsdidaktische Impulse für die Praxis des kokoRUs. Rezension zu Bernd Schröder/Jan Woppowa (Hg.): Theologie für den konfessionell-kooperativen Religionsunterricht. Ein Handbuch, Tübingen 2021 - Neumann, Anna (Praktische Theologie. Zeitschrift für Praxis in Kirche, Gesellschaft und Kultur)

Approximating a Laplacian Prior for Joint State and Model Estimation within an UKF - Götte, Ricarda-Samantha; Timmermann, Julia (IFAC-PapersOnLine)
Low-quality models that miss relevant dynamics lead to major challenges in modelbased state estimation. We address this issue by simultaneously estimating the system’s states and its model inaccuracies by a square root unscented Kalman filter (SRUKF). Concretely, we augment the state with the parameter vector of a linear combination containing suitable functions that approximate the lacking dynamics. Presuming that only a few dynamical terms are relevant, the parameter vector is claimed to be sparse. In Bayesian setting, properties like sparsity are expressed by a prior distribution. One common choice for sparsity is a Laplace distribution. However, due to disadvantages of a Laplacian prior in regards to the SRUKF, the regularized horseshoe distribution, a Gaussian that approximately features sparsity, is applied instead. Results exhibit small estimation errors with model improvements detected by an automated model reduction technique.
Keywords: joint estimation; unscented Kalman filter; sparsity; Laplacian prior; regularized horseshoe; principal component analysis

All optical operation of a superconducting photonic interface - Thiele, Frederik; Hummel, Thomas; McCaughan, Adam N.; Brockmeier, Julian; Protte, Maximilian; Quiring, Victor; Lengeling, Sebastian; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)
Quantum photonic processing via electro-optic components typically requires electronic links across different operation environments, especially when interfacing cryogenic components such as superconducting single photon detectors with room-temperature control and readout electronics. However, readout and driving electronics can introduce detrimental parasitic effects. Here we show an all-optical control and readout of a superconducting nanowire single photon detector (SNSPD), completely electrically decoupled from room temperature electronics. We provide the operation power for the superconducting detector via a cryogenic photodiode, and readout single photon detection signals via a cryogenic electro-optic modulator in the same cryostat. This method opens the possibility for control and readout of superconducting circuits, and feedforward for photonic quantum computing.
Keywords: Atomic and Molecular Physics; and Optics

Kompromisse vor dem Kompromiss: Friedensstiftung im hohen Mittelalter - Kamp, Hermann (Kompromissfindung in der Literatur und Kultur des Mittelalters: Strategien und Narrative zwischen Zweifel, Dissens und Aporie)

Investigation regarding the correlation of the relative influences during the extrusion process of cast films on the residual melt quality - Schöppner, Volker; Trienens, Dorte

Psychologie - Gretz, Daniela (Theodor-Fontane- Handbuch)

Rezeption zu Lebzeiten - Gretz, Daniela (Theodor- Fontane-Handbuch)

Beteiligung im Onlineunterricht in der Berufsfachschule. - Sommer, Sabrina; Förster, Anika (Therapie Lernen)

Schulkulturbezogene Schultypen im Zeitalter der digitalen Transformation. Eine Typologie unter Berücksichtigung von Hintergrundmerkmalen der zur Schulkultur befragten Lehrkräfte - Caruso, Carina; Drossel, Kerstin; Heldt, Melanie (MedienPädagogik)
In view of technological progress, a digitalisation deficit in German schools as well as the experiences in schools as a result of the Corona pandemic, it becomes apparent that the question of a school culture conducive to learning retains its relevance in the age of digital transformation: On the one hand, it is evident that school culture changes in view of the digital transformation. On the other hand, it contributes to the successful implementation of digital media. Previous research findings in connection with the digital transformation focus on particular competencies of teachers (Meyer, Becker, and Bock 2023; Caruso, Heldt, and Drossel 2022; Vogelsang et al. 2023) and their cooperative behaviour (Drossel and Heldt 2022; Schulze, Drossel, and Eickelmann 2022). These questions whether school culture-related school types can be identified or not and how teachers perceive the school culture have been less considered so far. This article is dedicated to this question and explores if the school culture-related school types differ in terms of the background characteristics of the teachers. Based on a Latent Class Analysis, three school culture-related school types become apparent: strong in innovation and cooperation (Type I: 45.74 %), highly innovative and inhibited cooperation (Type II: 17.95 %), inhibited in terms of innovation and cooperation (Type III: 36.31 %). The types do not differ from each other regarding the background characteristics.

Gemeindereferent_innen als Katalysator einer Transformation von Kirche? Professionsbezogene Perspektiven - Caruso, Carina; Hobelsberger, Hans (Gemeindereferent:in. Kompetenzen und Potenziale eines unterschäzten Berufs. Eine Studie zu Berufsbild und kirchlich-pastoraler Transformation)

Design und Ergebnisse des qualitativen Studienteils - Jung , Jennifer; Caruso, Carina (Gemeindereferent:in. Kompetenzen und Potenziale eines unterschätzten Berufs. Eine Studie zu Berufsbild und kirchlich-pastoraler Transformation)

Elisabetta Lupi, Jonathan Voges (Eds.), Luxus. Perspektiven von der Antike bis zur Neuzeit - Harnack, Maria

Forderer, Tanja, Was Gott zusammengefügt hat...? Eine argumentationsanalytische Untersuchung von Ehe-Scheidung im Neuen Testament am Beispiel von Mk 10,1–12 und 1Kor 7,10–16 - Breuer, Saskia Rebecca (Theologische Revue)

Einführung - Breuer, Saskia Rebecca; Paul, Clarissa; Schmidt, Eckart (Konflikte und Krisen im Neuen Testament und ihre Bewältigungsstrategien)

Leitlinien für einen armuts- und gendersensiblen Religionsunterricht. Reflexionshilfen zur Praxis inklusiver religiöser Bildung - Uppenkamp, Vera; Knauth, Thorsten (Religiöse Bildung an den Rändern der Vielfalt. Soziale Benachteiligung, Religion, Geschlecht)

Zwischen Inklusion und Distinktion. Armutssensibler Religionsunterricht unter Berücksichtigung genderbezogener Aspekte - Uppenkamp, Vera (Religiöse Bildung an den Rändern der Vielfalt. Soziale Benachteiligung, Religion, Geschlecht)

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

Wie entwickeln sich medienbezogene Einstellungen, selbsteingeschätzte Medienkompetenzen und motivationale Orientierungen angehender Lehrkräfte? - Vogelsang, Christoph; Caruso, Carina; Seifert, Andreas; Schwabl, Franziska (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Für die lernförderliche Einbindung digitaler Medien in schulische Lehr-Lern-Situationen sollten angehende Lehrkräfte neben mediendidaktischen sowie medienerzieherischen Kompetenzen auch über medienbezogene motivationale und volitionale Dispositionen verfügen. Insbesondere Einstellungen und selbsteingeschätzte Kompetenzen sind Einflussfaktoren auf die Motivation zur Mediennutzung. Auf Basis einer Sekundäranalyse wird daher in diesem Beitrag die wechselseitige Entwicklung dieser Dispositionen für verschiedene medienbezogene Kompetenzfacetten von N = 269 Lehramtsstudierenden längsschnittlich untersucht, die ein fünfmonatiges Langzeitpraktikum während der Massnahmen zur Eindämmung der CoViD-19-Pandemie im Wintersemester 2020/2021 absolviert haben. Diese Zeit ging mit vermehrten medienbezogenen Lerngelegenheiten einher. Die Ergebnisse zeigen, dass sich die Einstellungen der angehenden Lehrkräfte hinsichtlich der Mediennutzung kaum veränderten, sich selbsteingeschätzte Medienkompetenzen und medienbezogene Motivation hingegen mit kleinem bis mittlerem Effekt positiv entwickelten. Cross-Lagged-Panel-Analysen zeigen zudem, dass sich eine hohe motivationale Orientierung in Bezug auf die Mediennutzung zu Beginn des Langzeitpraktikums positiv auf die Entwicklung selbsteingeschätzter Kompetenzen auswirkte, allerdings nicht in allen in der Analyse betrachteten Kompetenzfacetten.
Keywords: Pharmacology

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

An eigenen Fällen lernen. Überlegungen zur lern- und entwicklungsorientierten Fallarbeit in der Religionslehrer:innenbildung - Caruso, Carina; Woppowa , Jan (Religionslehrer:in im 21. Jahrhundert. Transformationsprozesse im Beruf und theologisch-religionspädagogischer Bildung in Studium, Referendariat und Fortbildung)

Integrative conceptualization of products and business models for the circular economy: A systematic literature review - Scholtysik, Michel; Koldewey, Christian; Rohde, Malte; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Die Transformation zum Smart Service-Anbieter - Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman; Rasor, Anja; Ködding, Patrick; Wegel, Arthur; Fischer, Lena

Einstieg in die Kreislaufwirtschaft: Integrative Planung von Produkten und Geschäftsmodellen - Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman; Pierenkemper, Christoph; Hensen, Christian

A Data Map for Product Creation: Tasks, Data Flows, and IT-Systems from the Initial Idea to the Start of Production - Ködding, Patrick; Tissen, Denis; Koldewey, Christian (Proceedings of the 56th CIRP Conference on Manufacturing Systems, CIRP CMS ‘23)

A Framework For The Domain-Driven Utilization Of Manufacturing Sensor Data In Process Mining: An Action Design Approach - Brock, Jonathan; Rempe, Niclas; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (5th Conference on Production Systems and Logistics)

Conceptual Framework for Prescriptive Analytics based on decision Theory - Weller, Julian; Migenda, Nico; Wegel, Arthur; Kohlhase, Martin; Schenk, Wolfram; Dumitrescu, Roman (IEEE ADACIS 2023)

A Reference Process Model for Scenario-based Foresight - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the XXXII ISPIM Innovation Conference)

Enhancing Risk Management for Digitalisation Projects in the Context of Socio-Technical Systems - Menzefricke, Jörn Steffen; Koldewey, Christian; Dumitrescu, Roman (The Digital Twin of Humans)

Low temperature debonding of toughened structural adhesive joints: A new approach to repairs in the automotive industry - Bartley, Aurélie; Chudalla, Nick; Meschut, Gerson; Wibbeke, Tim Michael (International Journal of Adhesion and Adhesives)

Material-Preserving Extrusion of Polyamide on a Twin-Screw Extruder - Schöppner, Volker; Altepeter, Matthias; Schall, Christoph Wilhelm Theodor; Wanke, Sven; Kley, Marina (Polymers)

The Role of Design in interdisciplinary Product Development – Challenges, Research Approaches and Further Research needs - Stöhr, Bernd; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract In global competition, companies are continuously searching for a competitive advantage. A growing number of companies have identified the design of their products as a major success factor. The promises for companies associated with outstanding design are extremely attractive, ranging from better customer experience to higher sales growth. But even though the advantages of design seem to be compelling, companies are still having difficulties in leveraging the benefits of design. In this paper, we want to identify the underlying challenges that explain this gap. We are especially interested in the role and challenges of design in interdisciplinary product development. Therefore, we perform a literature review that clarifies terminology, analyses research approaches and identifies challenges. We determine seven key challenges for design in interdisciplinary product development. Furthermore, we observe a limited scope of research approaches in the reviewed literature. Based on these findings, we propose three further research directions to strengthen the role of design in interdisciplinary product development in the future.

Designing Business Models for a Circular Economy - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The megatrend sustainability will significantly change the future value creation of manufacturing companies. Their current linear value creation models need to change to conform to the requirements of sustainability. To face the challenges the circular economy has emerged as a promising economic model. With the shift from a linear to a circular economy, companies have to adjust their current business models. However, they still lack knowledge and adequate methods to develop circular business models. Hence, the aim of the paper is a circular business model canvas (CBMC) for designing circular businesses. A systematic literature review was conducted to identify significant criteria for circular business models. The criteria were analyzed utilizing a qualitative content analysis to derive the business model elements required for the circular economy. Existing elements from the Business Model Canvas were enriched and five new elements, e.g., reverse logistics, were found. Then, the business model elements were logically arranged resulting in the CBMC. It guides companies to systematically develop business models for the circular economy. The CBMC was evaluated by applying it within a mediumsized company in the electronics sector.

Model-based Systems Engineering using Security Design Patterns in the Context of ISO/SAE 21434 - Japs, Sergej; Faheem, Faizan; Anacker, Harald; Husung, Stephan; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of modern vehicles is complex, especially regarding compliance with security and safety. ISO/SAE 21434 considers security and safety along the entire product life cycle. According to the standard, a system architecture, a risk analysis, and the application of countermeasures are carried out in the early system design. Design patterns are solutions to known design problems. Security Design Patterns (SDP) describe countermeasures and are used to reduce risk. After our literature review, we did not find a suitable approach that presents SDPs that would be applicable in early system design. In this paper, we present 10 SDPs for early system design, which we evaluated during an 11-week student project with 28 teams. We present the results of the quantitative analysis and the evaluation of the feedback.